Multilayer electronic component
By using polydopamine in the covering part of the multilayer ceramic capacitor to form nitrogen-doped carbonized polydopamine, the problem of reduced mechanical strength and moisture resistance reliability is solved and higher mechanical strength and moisture resistance are achieved.
Patent Information
- Application Number
- CN202410738410.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-18
- Filing Date
- 2024-06-07
- Publication Date
- 2025-01-21
AI Technical Summary
The mechanical strength and moisture resistance of the multi-layer ceramic capacitors are reduced due to the decrease in the thickness of the cover, resulting in cracks and brittle fracture problems.
Polydopamine is used as the material of the covering part, and nitrogen-doped carbonized polydopamine is formed through its self-polymerization, which enhances the mechanical strength and toughness of the covering part, inhibits the expansion of cracks, and improves moisture resistance reliability.
It effectively improves the mechanical strength and moisture-resistant reliability of multi-layer electronic components, prevents crack expansion, and enhances the adhesive strength and moisture-proof performance of the covering part.
Smart Images

Figure CN119340110A_ABST
Abstract
Description
[0001] This application claims the benefit of priority from Korean Patent Application No. 10-2023-0139246 filed on October 18, 2023, in the Korean Intellectual Property Office, and Korean Patent Application No. 10-2023-0095529 filed on July 21, 2023, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein in their entirety by reference. Technical Field
[0002] The present disclosure relates to a multi-layer electronic assembly. Background Art
[0003] A multilayer ceramic capacitor (MLCC, a multilayer electronic component) may be a chip capacitor mounted on a printed circuit board of various electronic products (including image display devices such as liquid crystal displays (LCDs) and plasma display panels (PDPs), computers, smart phones, mobile phones, etc.) and used to charge or discharge therefrom. Since such a multilayer ceramic capacitor may have a small size and high capacitance and may be easily mounted, such a multilayer ceramic capacitor may be used as a component of various electronic devices.
[0004] Recently, in order to ensure the capacitance per unit volume of the multilayer ceramic capacitor, the multilayer ceramic capacitor has been miniaturized, and therefore, the thickness of the cover portion of the multilayer ceramic capacitor that protects the capacitance forming portion for forming the capacitance has been reduced. However, as the thickness of the cover portion is reduced, the mechanical strength of the multilayer ceramic capacitor may be weakened, which may cause cracks or brittle fractures in the multilayer ceramic capacitor. The cracks may become a path for external moisture to enter the multilayer ceramic capacitor, resulting in a decrease in the moisture resistance reliability of the multilayer ceramic capacitor.
[0005] Therefore, in order to prevent the mechanical strength and moisture resistance reliability of the multilayer ceramic capacitor from being reduced, it may be necessary to study the improvement of the hardness and toughness of the cover portion. Summary of the invention
[0006] Embodiments of the present disclosure are directed to providing a multilayer electronic component having improved mechanical strength and moisture resistance reliability.
[0007] According to an embodiment of the present disclosure, a multilayer electronic component includes: a main body, including a capacitor forming part and a covering part, the capacitor forming part including dielectric layers and internal electrodes alternately arranged in a first direction, the covering part is arranged on two surfaces of the capacitor forming part opposite to each other in the first direction; and an external electrode, arranged on the main body and connected to the internal electrode, wherein the covering part includes polydopamine. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] The above and other aspects, features and advantages of the present disclosure will be more clearly understood through the following detailed description in conjunction with the accompanying drawings, in which:
[0009] Figure 1 is a perspective view showing a multilayer electronic component according to an embodiment of the present disclosure;
[0010] Figure 2 It is shown Figure 1 An exploded perspective view of the main body of the embodiment shown in FIG.
[0011] Figure 3 It is shown along Figure 1 A cross-sectional view of a section taken along line II' in FIG.
[0012] Figure 4 It is shown along Figure 1 A cross-sectional view of a section taken along line II-II' in FIG.
[0013] Figure 5A is a diagram showing the chemical structure of dopamine hydrochloride;
[0014] Figure 5B is a diagram showing the chemical structure of polydopamine;
[0015] Figure 5C is a diagram showing the chemical structure of nitrogen-doped carbonized polydopamine;
[0016] Figure 6 It is shown Figure 3 An enlarged view of area K1 in FIG.
[0017] Figure 7 It is shown Figure 3 An enlarged view of region K2 in FIG.
[0018] Figure 8 It is shown Figure 6 An enlarged view of a region K3 in FIG. 1 , showing suppression of crack propagation by a cover portion for a multilayer electronic component according to an embodiment of the present disclosure;
[0019] Fig. 9 is a graph showing the results of analyzing a cover portion of a multilayer electronic component using an X-ray photoelectron spectroscopy (XPS) according to an embodiment;
[0020] Fig.10 is a graph showing the results of analyzing a cover portion of a multilayer electronic component using Raman analysis according to an embodiment;
[0021] Fig.11 is a graph showing the hardness measurement results of the comparative example and the embodiment;
[0022] Fig.12is a graph showing the toughness measurement results of the comparative example and the embodiment;
[0023] Fig.13A is a graph showing reliability evaluation results of a comparative example; and
[0024] Fig. 13B is a graph showing reliability evaluation results of an embodiment of the present disclosure. DETAILED DESCRIPTION
[0025] Hereinafter, embodiments of the present disclosure will be described with reference to the accompanying drawings.
[0026] These embodiments are described in sufficient detail to enable those skilled in the art to practice the present invention. It will be understood that the various embodiments of the present invention, although different, are not necessarily mutually exclusive. For example, without departing from the spirit and scope of the present disclosure, the structure, shape and size described as an example in one embodiment of the present disclosure may be implemented in another embodiment. In addition, without departing from the spirit and scope of the present disclosure, the position or arrangement of the elements in the embodiment may be modified. Therefore, the following detailed description should not be regarded as having a limiting meaning, and the scope of the present invention is limited only by the full scope of the attached claims and the equivalent schemes assigned by the claims, which are appropriately interpreted.
[0027] In the accompanying drawings, the same elements will be represented by the same reference numerals. In addition, redundant descriptions and detailed descriptions of known functions and elements that may unnecessarily obscure the subject matter of the present disclosure will be omitted. In the accompanying drawings, some elements may be exaggerated, omitted or briefly shown, and the size of the elements does not necessarily reflect the actual size of these elements. The terms "comprise", "comprising", "constructed to", etc. in the specification are used to represent the presence of features, quantities, steps, operations, elements, parts or combinations thereof, and do not exclude the possibility of combining or adding one or more features, quantities, steps, operations, elements, parts or combinations thereof.
[0028] In the drawings, a first direction may be defined as a thickness (T) direction, a second direction may be defined as a length (L) direction, and a third direction may be defined as a width (W) direction.
[0029] Multilayer electronic components
[0030] Figure 1 is a perspective view showing a multilayer electronic component according to an embodiment.
[0031] Figure 2 It is shown Figure 1 An exploded perspective view of the main body of the embodiment shown in FIG.
[0032] Figure 3 It is shown along Figure 1A cross-sectional view of a section taken along line II' in FIG.
[0033] Figure 4 It is shown along Figure 1 A cross-sectional view of a section taken along line II-II' in FIG.
[0034] Figure 5A is a diagram showing the chemical structure of dopamine hydrochloride.
[0035] Figure 5B is a diagram showing the chemical structure of polydopamine.
[0036] Figure 5C is a diagram showing the chemical structure of nitrogen-doped carbonized polydopamine.
[0037] Figure 6 It is shown Figure 3 Magnified view of area K1 in FIG.
[0038] Figure 7 It is shown Figure 3 Magnified view of area K2 in FIG.
[0039] Figure 8 It is shown Figure 6 FIG. 1 is an enlarged view of a region K3 in FIG. 1 , showing the suppression of crack propagation by the cover for the multilayer electronic component according to the embodiment.
[0040] Fig. 9 is a graph showing the results of analyzing a cover portion of a multilayer electronic component using an X-ray photoelectron spectroscopy (XPS) according to an embodiment.
[0041] Fig.10 is a graph showing the results of analyzing a cover portion of a multilayer electronic component using Raman analysis according to an embodiment.
[0042] In the following, reference will be made to Figures 1 to 10 A multilayer electronic component according to an embodiment is described in more detail. A multilayer ceramic capacitor will be described as an example of the multilayer electronic component, but embodiments thereof are not limited thereto.
[0043] The multilayer electronic component 100 may include a body 110 and external electrodes 131 and 132 .
[0044] The shape of the body 110 may not be limited to any particular shape, but Figure 1 As shown, the body 110 may have a hexahedral shape or a shape similar to a hexahedral shape. Due to shrinkage of ceramic powder included in the body 110 during the firing process and / or due to corner polishing, the body 110 may not have a precise hexahedral shape formed by straight lines, but may generally have a hexahedral shape.
[0045] The main body 110 may have a first surface 1 and a second surface 2 that face each other in a first direction, a third surface 3 and a fourth surface 4 that are connected to the first surface 1 and the second surface 2 and face each other in a second direction, and a fifth surface 5 and a sixth surface 6 that are connected to the first surface 1 and the second surface 2 and the third surface 3 and the fourth surface 4 and face each other in a third direction.
[0046] The main body 110 may include a dielectric layer 111, and a first internal electrode 121 and a second internal electrode 122. The first internal electrode 121 and the second internal electrode 122 are alternately arranged in the first direction, and the dielectric layer 111 is interposed between the first internal electrode 121 and the second internal electrode 122. The plurality of dielectric layers 111 forming the main body 110 may be in a fired state, and adjacent dielectric layers 111 may be integrated with each other, such that it is difficult to identify the boundary between adjacent dielectric layers 111 without using a scanning electron microscope (SEM).
[0047] The dielectric layer 111 may be formed by the following method: preparing a ceramic slurry including ceramic powder, an organic solvent, an additive, and a binder, preparing a green sheet by coating the ceramic slurry on a carrier film and drying the ceramic slurry, and firing the green sheet. The ceramic powder is not limited to any specific example as long as sufficient electrostatic capacitance can be obtained therefrom. Examples of the ceramic powder may include BaTiO3 or (Ba 1-x Ca x )TiO3 (0 < x < 1) in which Ca (calcium) and / or Zr (zirconium) is partially solid-solved in BaTiO3, Ba(Ti 1-y Ca y )O3 (0 < y < 1), (Ba 1-x Ca x )(Ti 1-y Zr y )O3 (0 < x < 1, 0 < y < 1), or Ba(Ti 1-y Zr y )O3 (0 < y < 1).
[0048] The internal electrodes 121 and 122 may include a first internal electrode 121 and a second internal electrode 122. The first internal electrode 121 and the second internal electrode 122 are alternately arranged in the first direction, and the dielectric layer 111 is interposed between the first internal electrode 121 and the second internal electrode 122. That is, the first internal electrode 121 and the second internal electrode 122, which are a pair of electrodes having different polarities, may be arranged to face each other with the dielectric layer 111 therebetween. The first internal electrode 121 and the second internal electrode 122 may be electrically separated from each other by the dielectric layer 111 disposed therebetween.
[0049] The first internal electrode 121 may be spaced apart from the fourth surface 4 and may be connected to the first external electrode 131 on the third surface 3 side. The second internal electrode 122 may be spaced apart from the third surface 3 and may be connected to the second external electrode 132 on the fourth surface 4 side.
[0050] The conductive metal included in the internal electrodes 121 and 122 may be one or more of Ni, Cu, Pd, Ag, Au, Pt, Sn, W, Ti, and alloys thereof, and more preferably, may include Ni, but the embodiment is not limited thereto.
[0051] The internal electrodes 121 and 122 may be formed by coating a conductive paste (including a conductive metal) for internal electrodes on a ceramic green sheet to a predetermined thickness and firing the conductive paste for internal electrodes. The conductive paste for internal electrodes may be printed by screen printing or gravure printing, but the embodiment is not limited thereto.
[0052] The average thickness td of the dielectric layer 111 and the average thickness te of the internal electrodes 121 and 122 do not need to be limited to any specific example. The average thickness td of the dielectric layer 111 may be, for example, 0.1 μm to 10 μm. The average thickness te of the internal electrodes 121 and 122 may be, for example, 0.1 μm to 3.0 μm. In addition, the average thickness td of the dielectric layer 111 and the average thickness te of the internal electrodes 121 and 122 may be arbitrarily determined according to the desired characteristics or purpose. For example, in the case of a high-voltage electronic component for miniaturization and high capacitance, the average thickness td of the dielectric layer 111 may be less than 2.8 μm, and the average thickness te of the internal electrodes 121 and 122 may be less than 1 μm. In addition, in the case of a small information technology (IT) electronic component for miniaturization and high capacitance, the average thickness td of the dielectric layer 111 may be less than or equal to 0.4 μm, and the average thickness te of the internal electrodes 121 and 122 may be less than or equal to 0.4 μm.
[0053] The average thickness td of the dielectric layer 111 and the average thickness te of the internal electrodes 121 and 122 may represent the average size of the dielectric layer 111 in the first direction and the average size of the internal electrodes 121 and 122 in the first direction, respectively. The average thickness td of the dielectric layer 111 and the average thickness te of the internal electrodes 121 and 122 may be measured by scanning the cross section of the main body 110 in the first direction and the second direction using a scanning electron microscope (SEM) with a magnification of 10000 and obtained by measuring the thickness at a plurality of points of the dielectric layer 111 (e.g., 30 points spaced at equal distances in the second direction). In addition, the average thickness te of the internal electrodes 121 and 122 may be obtained by measuring the thickness at a plurality of points of one internal electrode 121 or 122 (e.g., 30 points spaced at equal distances in the second direction). The 30 points spaced at equal distances may be specified in the capacitance forming portion Ac. The average thickness td of the dielectric layer 111 and the average thickness te of the internal electrodes 121 and 122 may be more generalized by calculating an average after measuring the thickness of ten dielectric layers 111 respectively and calculating an average after measuring the thickness of ten internal electrodes 121 and 122 respectively.
[0054] The body 110 may include covering portions 112 and 113 disposed on two surfaces of the capacitance forming portion Ac that are opposite to each other in the first direction. The body 110 may include a first covering portion 112 disposed on the first surface 1 side and a second covering portion 113 disposed on the second surface 2 side. The covering portions 112 and 113 may mainly prevent damage to the internal electrode due to physical stress and / or chemical stress. The covering portions 112 and 113 do not include the internal electrode and may be constructed similarly to the dielectric layer 111.
[0055] The average thickness tc of the covering portions 112 and 113 need not be limited to any particular example. That is, the average thickness tc of the covering portions 112 and 113 may be arbitrarily determined according to the desired characteristics or purpose. For example, for miniaturization and high capacitance of multilayer electronic components, the average thickness tc of the covering portions 112 and 113 may be less than or equal to 300 μm, less than or equal to 100 μm, less than or equal to 30 μm, or less than or equal to 20 μm, but embodiments thereof are not limited thereto. Here, the average thickness tc of the covering portions 112 and 113 may represent the average thickness of each of the first covering portion 112 and the second covering portion 113.
[0056] The average thickness tc of the covering portions 112 and 113 may indicate an average size of the covering portions 112 and 113 in the first direction, and may be an average value of the size of the covering portions in the first direction at five points spaced apart from each other at equal intervals in the second direction measured in a cross section of the body 110 in the first and second directions.
[0057] The cover portions 112 and 113 may be formed by laminating at least one ceramic green sheet (without forming an internal electrode pattern) for forming the cover portions on both surfaces of the capacitance forming portion Ac facing each other in the first direction and firing the ceramic green sheet.
[0058] The body 110 may include edge portions 114 and 115 disposed on two surfaces of the capacitance forming portion Ac that are opposite to each other in the third direction. The body 110 may include a first edge portion 114 disposed on the fifth surface 5 side and a second edge portion 115 disposed on the sixth surface 6 side. The edge portions 114 and 115 may refer to regions between both ends of the internal electrodes 121 and 122 and the outer surface of the body 110 in a cross section of the body 110 in the first direction and the third direction.
[0059] The edge portions 114 and 115 do not include the internal electrodes 121 and 122, and may be configured similarly to the dielectric layer 111. The edge portions 114 and 115 may mainly prevent damage to the internal electrodes 121 and 122 due to physical stress and / or chemical stress.
[0060] The edge portions 114 and 115 may be formed by not coating the conductive paste on the ceramic green sheet when forming the internal electrodes 121 and 122 by coating the conductive paste on the ceramic green sheet, and then firing. Alternatively, in order to suppress the step difference formed by the internal electrodes 121 and 122, the edge portions 114 and 115 may be formed by cutting the laminated body after laminating the ceramic green sheets on which the conductive paste for the internal electrodes is coated to expose the internal electrodes 121 and 122 to two surfaces of the capacitor forming portion blank facing each other in the third direction, and laminating a single dielectric layer or two or more dielectric layers on two surfaces of the capacitor forming portion blank facing each other in the third direction.
[0061] The average thickness tm of the edge portions 114 and 115 need not be limited to any specific example. That is, the average thickness tm of the edge portions 114 and 115 can be arbitrarily determined according to the desired characteristics or purpose. For example, for the miniaturization and high capacitance of the multilayer electronic component, the average thickness tm of the edge portions 114 and 115 may be less than or equal to 100 μm, less than or equal to 20 μm, or less than or equal to 15 μm, but the embodiment is not limited thereto. Here, the average thickness tm of the edge portions 114 and 115 may refer to the average thickness of each of the first edge portion 114 and the second edge portion 115.
[0062] The average thickness tm of the edge portions 114 and 115 may refer to the average size of the edge portions 114 and 115 in the third direction, and may be the average value of the size of the edge portions in the third direction at five points spaced apart from each other at equal distances measured in a cross-section of the body 110 in the first and third directions.
[0063] The external electrodes 131 and 132 may be disposed on the body 110 and may be connected to the internal electrodes 121 and 122. The external electrodes 131 and 132 may be disposed on the third surface 3 and the fourth surface 4 of the body 110 and may extend to a portion of the first surface 1, a portion of the second surface 2, a portion of the fifth surface 5, and a portion of the sixth surface 6. The external electrodes 131 and 132 may include a first external electrode 131 connected to the first internal electrode 121 and a second external electrode 132 connected to the second internal electrode 122.
[0064] The first external electrode 131 may include: a first electrode layer 131a disposed on the third surface 3 of the body 110 and directly connected to the first internal electrode 121; and a second electrode layer 131b disposed on the first electrode layer 131a. The second external electrode 132 may include: a first electrode layer 132a disposed on the fourth surface 4 of the body 110 and directly connected to the second internal electrode 122; and a second electrode layer 132b disposed on the first electrode layer 132a.
[0065] The first electrode layers 131a and 132a may be formed by dipping the third surface 3 and the fourth surface 4 of the body 110 into a conductive paste for an external electrode (including a conductive metal and glass) and firing. The conductive metal included in the first electrode layers 131a and 132a may include Cu, Ni, Pd, Pt, Au, Ag, Pb, and / or an alloy thereof, but the embodiment is not limited thereto.
[0066] In addition, the first electrode layers 131a and 132a may include only a layer including metal and glass, but the embodiment is not limited thereto, and the first electrode layers 131a and 132a may have a multi-layer structure. For example, the first electrode layers 131a and 132a may include: a first layer including metal and glass; and a second layer provided on the first layer and including metal and resin.
[0067] The metal included in the second layer is not limited to any specific example, and may include one or more selected from the group consisting of Ni, Cu, Pd, Ag, Au, Pt, Sn, W, Ti, and alloys thereof. The resin included in the second layer can ensure adhesion and can be used as a shock absorber. The resin is not limited to any specific example as long as the resin has adhesive properties and shock absorbing properties and can be mixed with metal powder to form a paste. For example, the resin may include one or more types of resins selected from epoxy resins, acrylic resins, ethyl cellulose, etc.
[0068] The second electrode layers 131b and 132b may improve mounting characteristics. The types of the second electrode layers 131b and 132b are not limited to any specific example, and may be a plating layer including Ni, Sn, Pd, and / or an alloy containing them, and may be formed into a plurality of layers. The second electrode layers 131b and 132b may be, for example, a Ni plating layer or a Sn plating layer, or may be formed by sequentially forming a Ni plating layer and a Sn plating layer. In addition, the second electrode layers 131b and 132b may include a plurality of Ni plating layers and / or a plurality of Sn plating layers.
[0069] In the drawings, the multilayer electronic component 100 may have two external electrodes 131 and 132 , but embodiments thereof are not limited thereto, and the number and shape of the external electrodes 131 and 132 may vary according to the shapes of the internal electrodes 121 and 122 and / or other purposes.
[0070] According to an embodiment, the covering parts 112 and 113 may include polydopamine. Polydopamine may be a polymer of dopamine. Polydopamine formed by self-polymerization of dopamine has covalent catechol and imine functional groups and may form strong bonds with inorganic materials (such as ceramic powder) and organic materials (such as adhesives).
[0071] As will be described later, a ceramic green sheet for forming the cover portions 112 and 113 may be added to the sheet for forming the cover portions 112 and 113 of the multilayer electronic component 100 according to the embodiment (ie, the ceramic green sheet for forming the cover portions). Figure 5A The dopamine hydrochloride added to the sheet material for forming the cover portion can be formed by polymerization. Figure 5B By including polydopamine, the sheet for forming the cover can form a strong bond with the ceramic powder and / or binder included in the sheet for forming the cover, and thus, the bonding strength of the sheet for forming the cover can be improved. Therefore, when the ceramic green sheets for forming the cover are stacked to form the covers 112 and 113, delamination or cracks between the sheets can be prevented, and the heat and pressure applied during the lamination process and the pressing process can be reduced.
[0072] Through the firing process for forming the body 110 of the multilayer electronic component 100, all or part of the polydopamine included in the sheet for forming the cover may be converted into Figure 5C In the embodiment, at least a portion of the polydopamine included in the covering portions 112 and 113 may be nitrogen-doped carbonized polydopamine. The nitrogen-doped carbonized polydopamine included in the covering portions 112 and 113 may be a two-dimensional material capable of improving the elastic modulus and toughness of the covering portions 112 and 113, and thus, the expansion of cracks generated in the covering portions 112 and 113 may be suppressed. Therefore, the mechanical strength of the multilayer electronic component 100 may be improved, and ultimately the moisture resistance reliability of the multilayer electronic component 100 may be improved.
[0073] In one embodiment, the atomic percentage of nitrogen included in the covers 112 and 113 relative to all elements included in the covers 112 and 113 may be greater than 0 at% and less than or equal to 3 at%. Among the elements (e.g., C, N, Ba, O, and Ti) included in the covers 112 and 113, nitrogen may be derived from nitrogen-doped carbonized polydopamine. When the atomic percentage of nitrogen included in the covers 112 and 113 relative to all elements included in the covers 112 and 113 exceeds 3 at%, the polydopamine content may be excessive, so that brittle fracture may occur due to the formation of agglomerates.
[0074] It is not necessary to limit the method of measuring the atomic percentage of nitrogen included in the covers 112 and 113 relative to the total elements included in the covers 112 and 113. For example, the nitrogen content may be measured by obtaining an image by scanning a cross section of the body 110 in the first direction and the second direction using a transmission electron microscope (TEM) or a scanning electron microscope (SEM), analyzing five points in the covers 112 and 113 spaced apart from each other at equal intervals in the second direction using an energy dispersive spectrometer (EDS), obtaining the atomic percentage of nitrogen included in the covers 112 and 113 relative to the total elements included in the covers 112 and 113 at each point, and calculating an average value (at%).
[0075] In the following, reference will be made to Figure 6 The cover portion is described in more detail. Figure 6 11 is an enlarged view showing a portion of the second cover portion 113 , and since the configurations of the first cover portion 112 and the second cover portion 113 are substantially the same, the following description may include descriptions of the first cover portion 112 and the second cover portion 113 .
[0076] Reference Figure 6, the covering portion may include a plurality of dielectric grains G1 and a grain boundary GB1 disposed between adjacent dielectric grains G1, and the polydopamine included in the covering portion may be disposed at the grain boundary GB1. The polydopamine disposed at the grain boundary GB1 may effectively block the expansion of cracks. In addition, the nitrogen-doped carbonized polydopamine may be hydrophobic, and since the nitrogen-doped carbonized polydopamine is disposed at the grain boundary GB1, the nitrogen-doped carbonized polydopamine may be used as a barrier to prevent moisture penetration. The presence of polydopamine (e.g., nitrogen-doped carbonized polydopamine) at the grain boundary GB1 may be indicated by the presence of N as determined by SEM-EDS. Even if not described in the present disclosure, other methods and / or other tools understood by a person of ordinary skill in the art may be used.
[0077] Reference Figure 8 , when the crack CR extends to the grain boundary GB1 existing between the dielectric grains G1, such as τ S (τ S =μN R , where τ S : Friction sliding stress, μ: Dynamic friction, N R : The force of the residual clamping stress) may be consumed as energy. In this case, when polydopamine with a high elastic modulus exists at the grain boundary GB1, the μ value may increase. That is, when polydopamine with a high elastic modulus exists at the grain boundary GB1, the expansion of the crack may consume more energy, and thus the expansion of the crack may be effectively prevented.
[0078] The nitrogen-doped carbonized polydopamine disposed at the grain boundary GB1 may induce densification of the cover 113 by suppressing grain growth of the dielectric grains G1. The average size of the plurality of dielectric grains G1 included in the cover 113 may be, for example, greater than or equal to 170 nm and less than or equal to 200 nm.
[0079] like Figure 7 As shown, the dielectric layer 111 may include a plurality of dielectric grains G2 and grain boundaries GB2 disposed between adjacent dielectric grains G2. The average size of the plurality of dielectric grains G2 included in the dielectric layer 111 need not be limited to any particular example. The average size of the plurality of dielectric grains G2 included in the dielectric layer 111 may be greater than or equal to the average size of the plurality of dielectric grains G1 included in the cover 113. In this case, there may be an advantage in improving the capacitance of the multilayer electronic component 100. However, embodiments thereof are not limited thereto, and the average size of the plurality of dielectric grains G2 included in the dielectric layer 111 may be smaller than the average size of the plurality of dielectric grains G1 included in the cover 113. In this case, there may be an advantage in improving the reliability of the multilayer electronic component 100.
[0080] The average size of the plurality of dielectric grains G1 included in the cover 113 may be, for example, an average value of grain sizes obtained by obtaining a central region (e.g., Figure 3 An image of the area K1 in FIG. 5 is taken at a magnification of 50,000 times, and the image is analyzed using an image analysis program (eg, the Zootos program from Zootos).
[0081] In addition, the average size of the plurality of dielectric grains G2 included in the dielectric layer 111 may be, for example, an average value of grain sizes obtained by obtaining, using a scanning electron microscope (SEM), a cross section in the first direction and the second direction cut from the center of the multilayer electronic component 100 in the third direction, a central region (e.g., Figure 3 An image of the dielectric layer 111 in the region K2 in FIG. 1 is taken at a magnification of 50,000 times, and the image is analyzed using an image analysis program (eg, the Zootos program from Zootos).
[0082] Reference Fig. 9 In an embodiment, when the covering portions 112 and 113 are analyzed using an X-ray photoelectron spectrometer (XPS), an N1s peak and a C1s peak may be detected. When the covering portions 112 and 113 include nitrogen-doped carbonized polydopamine, in addition to the Ba3d5 peak, the O1s peak, the Ti2p peak, and the C1s peak, the N1s peak may be detected. That is, when the N1s peak and the C1s peak are simultaneously detected during the XPS analysis, it may be determined that nitrogen-doped carbonized polydopamine is present in the covering portions 112 and 113. On the other hand, the intensity of the N1s peak may have a maximum value at a binding energy of 395 eV to 405 eV, and the intensity of the C1s peak may have a maximum value at a binding energy of greater than or equal to 280 eV and less than or equal to 290 eV, but embodiments thereof are not limited thereto.
[0083] XPS analysis of the covers 112 and 113 may be performed on outer surfaces of the covers 112 and 113 , but embodiments are not limited thereto and may also be performed on a cross section in the first and second directions polished to a central portion of the multilayer electronic component 100 in the third direction.
[0084] Reference Fig.10 In an embodiment, during the Raman analysis of the cover portions 112 and 113, a Raman shift of 1360 cm -1 Up to 1380cm -1 The first peak X was detected at 1610 cm -1 Up to 1630cm -1The first peak X may refer to a D peak, and the second peak Y may refer to a G peak. During Raman analysis of the cover portions 112 and 113, the first peak X and the second peak Y may appear simultaneously because the cover portions 112 and 113 may have a carbonized polydopamine structure having a two-dimensional structure.
[0085] In an embodiment, the ratio of the maximum intensity of the first peak X to the maximum intensity of the second peak Y may be greater than or equal to 0.01 and less than or equal to 1.50. The ratio of the maximum intensity of the first peak X to the maximum intensity of the second peak Y may vary according to the degree of defects in the carbonized polydopamine and / or the degree of nitrogen doping.
[0086] In an embodiment, the full width at half maximum of the first peak X may be greater than or equal to 80 cm -1 And less than or equal to 90cm -1 , and the full width at half maximum of the second peak Y can be greater than or equal to 100cm -1 And less than or equal to 110cm -1 The half maximum full width may refer to the full width of the peak at a point where the intensity is half of the maximum intensity. The half maximum full width of the first peak X and the half maximum full width of the second peak Y may vary depending on the degree of defects in the carbonized polydopamine and / or the degree of nitrogen doping.
[0087] Raman analysis of the covers 112 and 113 may be performed on outer surfaces of the covers 112 and 113 , but embodiments thereof are not limited thereto and may also be performed on cross sections in the first and second directions polished until a central portion of the multilayer electronic component 100 in the third direction.
[0088] In an embodiment, the dielectric layer 111 may not include polydopamine. When the dielectric layer 111 includes polydopamine, the mechanical strength of the dielectric layer 111 may be improved, but when polydopamine is included in the dielectric layer 111, which is directly related to the electrical characteristics of the multilayer electronic component 100, side effects such as degradation of the breakdown voltage of the multilayer electronic component 100 may occur.
[0089] When the dielectric layer 111 does not include (contains) polydopamine, nitrogen is not detected in the dielectric layer 111. In addition, when the dielectric layer 111 is analyzed using an X-ray photoelectron spectrometer (XPS), the N1s peak is not detected. In addition, when the dielectric layer 111 is subjected to Raman analysis, a peak at 1360 cm -1 Up to 1380cm -1 The Raman shift of 1610 cm -1 Up to 1630cm -1 No peak will be detected at at least one of the Raman shifts.
[0090] In an embodiment, the dielectric layer 111 may include a content of polydopamine less than the content of polydopamine included in the covering portions 112 and 113. In the present disclosure, the content of polydopamine in a portion refers to the weight percentage of polydopamine in the portion, and the comparison of the content of polydopamine in different portions may be performed by the atomic percentage of nitrogen in different portions, or may be performed by the lightness and darkness of the color. As an example, when the dielectric layer includes a content of polydopamine less than the content of polydopamine included in the covering portion, the dielectric layer may have a brighter color than the color of the covering portion, or the atomic percentage of nitrogen in the dielectric layer may be less than the atomic percentage of nitrogen in the covering portion, but is not limited thereto. When polydopamine is added to the dielectric layer 111 to improve the mechanical strength of the dielectric layer 111, a content of polydopamine less than the content of polydopamine included in the covering portions 112 and 113 may be added to prevent the electrical characteristics of the multilayer electronic component 100 from deteriorating. When the dielectric layer 111 includes polydopamine, the polydopamine may be disposed at the grain boundary GB2 of the dielectric layer 111 .
[0091] When the dielectric layer 111 includes polydopamine, during Raman analysis of the dielectric layer 111, the -1 Up to 1380cm -1 The third peak can be detected at the Raman shift of 1610 cm -1 Up to 1630cm -1 Since the dielectric layer 111 includes less polydopamine than the content of polydopamine included in the cover parts 112 and 113, the intensity of the third peak may be lower than the intensity of the first peak X, and the intensity of the fourth peak may be lower than the intensity of the second peak Y, but the embodiment is not limited thereto.
[0092] (Test example)
[0093] <Production Samples>
[0094] A ceramic slurry is prepared by mixing BaTiO3 powder, an organic solvent (such as ethanol) and a binder (such as polyvinyl butyral), applying the ceramic slurry to a carrier film and drying the ceramic slurry to prepare a ceramic green sheet. Thereafter, a conductive paste (including Ni powder and a binder) for an internal electrode is applied to the ceramic green sheet at a predetermined thickness.
[0095] Thereafter, ceramic green sheets for covering parts on which internal electrode patterns are not formed are stacked, dozens to hundreds of ceramic green sheets including internal electrode patterns are stacked, ceramic green sheets for covering parts on which internal electrode patterns are not formed are stacked, and a pressing process, a cutting process, and a firing process are performed to form a main body.
[0096] In this case, in the comparative example, dopamine hydrochloride is not added to the ceramic slurry used to form the ceramic green sheet for the covering portion. In Example 1, 0.5 parts by weight of dopamine hydrochloride is added to 100 parts by weight of the total ceramic slurry to form the ceramic green sheet for the covering portion. In Example 2, 1 part by weight of dopamine hydrochloride is added to 100 parts by weight of the total ceramic slurry to form the ceramic green sheet for the covering portion. As the weight of the added dopamine hydrochloride (i.e., the weight percentage of the added dopamine hydrochloride in the total ceramic slurry) increases, the atomic percentage of nitrogen in the final product (i.e., the atomic percentage of nitrogen included in the covering portion relative to the atomic percentage of all elements included in the covering portion) increases. However, when the weight percentage of the added dopamine hydrochloride exceeds 1wt%, or the atomic percentage of nitrogen in the final product exceeds 3at%, brittle fracture may occur due to the formation of agglomerates.
[0097] After that, the body was immersed in a conductive paste prepared by mixing Cu powder, glass frit, binder and solvent and fired to form a first electrode layer, and a Ni plating layer and a Sn plating layer were sequentially formed on the first electrode layer to form a second electrode layer. Thus, sample sheets for Comparative Example, Example 1 and Example 2 were prepared.
[0098] <Evaluation of hardness and toughness>
[0099] After that, the hardness and toughness of the cover portion of each sample were evaluated.The hardness and toughness of the cover portion were measured on the outer surface of the cover portion using a Vickers hardness tester, and 20 sample pieces in each of Comparative Example, Example 1, and Example 2 were evaluated.
[0100] Fig.11 It is a graph showing the hardness measurement results of Comparative Examples and Examples. Fig.12 It is a graph showing the toughness measurement results of Comparative Examples and Examples.
[0101] Reference Fig.11 and Fig.12 It can be confirmed that the hardness and toughness are improved in Examples 1 and 2 as compared with the Comparative Example. Samples in which more than 1 part by weight of dopamine hydrochloride was added per 100 parts by weight of the ceramic slurry to form a ceramic green sheet for a cover portion were also evaluated, but the hardness and toughness values were not measured due to brittle fracture of the sample sheets (this is due to the influence of agglomerates caused by the excessive dopamine hydrochloride content).
[0102] <Evaluation of Moisture Resistance Reliability>
[0103] After that, moisture resistance reliability was evaluated for the sample pieces of the comparative example and the sample pieces of Example 2. The moisture resistance reliability was evaluated by applying a temperature of 85° C., a humidity of 85%, and a voltage of 3.75 V for 8 hours to each of 400 sample pieces of each of the comparative example and Example 2, and measuring a change in insulation resistance (IR).
[0104] Fig.13A is a graph showing the reliability evaluation results of the comparative example, and Fig. 13B Graph showing the reliability evaluation results of Example 2 (an example of the present disclosure). Fig.13A and Fig. 13B , it can be confirmed that the insulation resistance (IR) of the sample in the comparative example initially decreases rapidly compared to that in the example 2. In other words, since the hydrophobic nitrogen-doped carbonized polydopamine is located at the grain boundary and acts as a barrier to prevent moisture penetration, the moisture resistance reliability in the example 2 is improved compared to that in the comparative example.
[0105] According to the aforementioned embodiments, a multilayer electronic component having excellent mechanical strength and moisture resistance reliability can be provided.
[0106] The embodiments do not necessarily limit the scope of the embodiments to the form of specific embodiments. On the contrary, modifications, equivalents and alternatives included in the disclosed concepts and technical scope of this specification may be adopted. Throughout the specification, similar reference numerals are used for similar elements.
[0107] In the embodiments, the term "embodiment" may not refer to the same embodiment, and may be provided to describe and emphasize the unique features of each embodiment. The embodiments set forth above may be implemented without excluding the possibility of combining the features of the embodiments set forth above with those of other embodiments. For example, unless otherwise specified, even if a feature described in an embodiment is not described in another embodiment, the description may be understood to be related to another embodiment.
[0108] The terms "first," "second," etc. may be used to distinguish one element from another, and may not limit the order and / or importance associated with the elements, etc. In some cases, a first element may be referred to as a second element, and similarly, a second element may be referred to as a first element, without departing from the scope of example embodiments.
[0109] While embodiments have been shown and described above, it will be readily apparent to those skilled in the art that modifications and variations may be made without departing from the scope of the present disclosure as defined by the appended claims.
Claims
1. A multilayer electronic component comprising: a main body including a capacitance forming part including a dielectric layer and an inner electrode alternately arranged in a first direction, and a covering part provided on two surfaces of the capacitance forming part opposite to each other in the first direction; and an outer electrode disposed on the body and connected to the inner electrode, Wherein, the covering portion comprises polydopamine.
2. The multilayer electronic component according to claim 1, wherein At least a portion of the polydopamine included in the cover is nitrogen-doped carbonized polydopamine.
3. The multilayer electronic component according to claim 1, wherein: An atomic percentage of nitrogen included in the covering portion is greater than 0 at % and less than or equal to 3 at % with respect to all elements included in the covering portion.
4. The multilayer electronic component according to claim 1, in, The covering portion includes a plurality of dielectric grains and grain boundaries disposed between adjacent dielectric grains, and Wherein, the polydopamine included in the covering portion is disposed at at least one of the grain boundaries.
5. The multilayer electronic component according to claim 1, in, The covering portion includes a plurality of dielectric grains and grain boundaries disposed between adjacent dielectric grains, and Wherein, an average size of the plurality of dielectric grains included in the covering portion is greater than or equal to 170 nm and less than or equal to 200 nm.
6. The multilayer electronic component according to claim 1, wherein: In the cover portion, when analyzed using an X-ray photoelectron spectrometer, an N1s peak and a C1s peak were detected.
7. The multilayer electronic component according to claim 1, wherein: During the Raman analysis of the cover, the -1 Up to 1380cm -1 The first peak was detected at the Raman shift of 1610 cm -1 Up to 1630cm -1 A second peak was detected at the Raman shift of .
8. The multilayer electronic component according to claim 7, wherein: A ratio of the maximum intensity of the first peak to the maximum intensity of the second peak is greater than or equal to 0.01 and less than or equal to 1.
50.
9. The multilayer electronic component according to claim 7, wherein: The full width at half maximum of the first peak is greater than or equal to 80 cm -1 And less than or equal to 90cm -1 , and the half-maximum width of the second peak is greater than or equal to 100 cm -1 And less than or equal to 110cm -1 .
10. The multilayer electronic component according to claim 1, wherein The dielectric layer does not contain polydopamine.
11. The multilayer electronic component according to claim 1, wherein The dielectric layer includes polydopamine, and a weight percentage of the polydopamine included in the dielectric layer is less than a weight percentage of the polydopamine included in the covering part.
12. The multilayer electronic component according to claim 1, wherein During analysis using an X-ray photoelectron spectrometer, an N1s peak was detected in the cover portion, and the N1s peak was not detected in the dielectric layer.
13. The multilayer electronic component according to claim 1, wherein During Raman analysis, in the overlay, the -1 Up to 1380cm -1 The first peak was detected at the Raman shift of 1610 cm -1 Up to 1630cm -1 A second peak was detected at the Raman shift of 1360 cm-1 in the dielectric layer. -1 Up to 1380cm -1 The Raman shift of 1610 cm -1 Up to 1630cm -1 No peak is detected at at least one of the Raman shifts.
14. The multilayer electronic component according to claim 1, in, During Raman analysis, in the overlay, the -1 Up to 1380cm -1 The first peak was detected at the Raman shift of 1610 cm -1 Up to 1630cm -1 A second peak was detected at the Raman shift of 1360 cm-1 and in the dielectric layer at 1360 cm-1. -1 Up to 1380cm -1 The third peak was detected at the Raman shift of 1610 cm -1 Up to 1630cm -1 A fourth peak was detected at the Raman shift of The intensity of the third peak is lower than that of the first peak, and the intensity of the fourth peak is lower than that of the second peak.
15. The multilayer electronic component according to claim 1, wherein at least a portion of the polydopamine included in the cover portion is nitrogen-doped carbonized polydopamine, The atomic percentage of nitrogen in the covering portion relative to all elements in the covering portion is greater than 0 at% and less than or equal to 3 at%, The covering portion includes a plurality of dielectric grains and grain boundaries arranged between adjacent dielectric grains, and Wherein, an average size of the plurality of dielectric grains included in the covering portion is greater than or equal to 170 nm and less than or equal to 200 nm.
16. The multilayer electronic component according to claim 15, wherein The dielectric layer does not contain polydopamine.
17. The multilayer electronic component according to claim 15, wherein: The dielectric layer includes polydopamine, and Wherein, a weight percentage of polydopamine included in the dielectric layer is less than a weight percentage of polydopamine included in the covering portion.
Citation Information
Patent Citations
Grain drink antibacterial test
KR1020230095529A
Composition for heat dissipation pad of semiconductor and heat dissipation system for semiconductor
KR1020230139246A